LOKAKARYA KOMUNITAS BELAJAR SEBAGAI UPAYA MENGUATKAN KERJA SAMA GURU YANG BERPUSAT PADA PESERTA DIDIK DI WILAYAH KALIMANTAN UTARA - Ilham, Muhammad Ilham; Iva Ani Wijiati; Dwi Cahyono Aji (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2024)
The transformation of education in Indonesia continues with various efforts to improve the quality of learning. One important initiative is the implementation of learning community workshops which aim to strengthen collaboration between teachers with a focus on students. This community service aims to carry out learning community workshops to improve teacher collaboration and the quality of learning. Activities were carried out in North Kalimantan with teachers from Tunas Rimba Kindergarten, Nurul Jadid Kindergarten, Hidayatullah IT Kindergarten, and Amustaqim IT Kindergarten. Implementation of activities generally consists of three stages: pre-activity, activity time, and post-activity. The results of the activities showed that the learning community workshop succeeded in creating a collaborative environment that supported the exchange of ideas and best practices between teachers. Participating teachers reported improvements in teaching skills, a better understanding of student needs, and the ability to design more interactive and effective lessons. Apart from that, this workshop also facilitated the formation of a strong working network between teachers, which contributed to improving the quality of education in North Kalimantan.